Organotin compounds - Okoro, HK; Fatoki, Olalekan S; Adekola, Folahan A; Ximba, Bhekumusa J; Snyman, Reinette G (Academic Press, 2014)
The use of tributyltin (TBT) and triphenyltin (TPT) as antifouling agents on boats has been widespread because of their superior effectiveness compared to previously used copper oxide paints. TBT is a biocide and catalyst used globally. TBT compounds have particularly been used as biocides in antifouling paints and wood preservatives. TBT leachate has contaminated both marine and freshwater habitats and it has been considered to be one of the most toxic agents entering the environment. The occurrence of TBT in surface water and sediment has prompted a large number of studies on its adverse effects on nontarget organisms. By the mid-1980s, it had become widely recognized that TBT severely affects nontarget organisms. Abnormal shell thickening has been reported in the Pacific oyster Crassostrea gigas associated with areas of high TBT contamination. Other adverse effects of TBT on organisms include imposex in gastropods. As well as being an endocrine-disrupting agent TBT has proven to be extremely toxic to a number of aquatic organisms, in particular during sensitive early life stages. It was revealed that TBT can induce cytogenetic damage in the embryos and larvae of the marine mollusc Mytilus edulis and the polychaete worm Platynereis dumerilii. Very limited work has been done on the genotoxic potential of TBT to adult marine organisms. In algae, for instance, triorganotins had the strongest influence on their growth and the least on their chlorophyll content.